Immunomodulatory effects of chemokines during the early implantation window - Fraccaroli, Laura Virginia (2009)
Successful implantation requires a functionally normal embryo at the blastocyst stage and a receptive endometrium as well as adequate communication between them throughout the implantation process. This cross-talk is highly regulated by a number of different kinds of molecules. Particularly, chemokines, small polypeptides that attract specific leukocyte subsets by binding to cell-surface receptors, are also required to maintain immune-privileged sites as the feto-maternal interface. Chemokines expression involves an interdependent network with the absence of a single chemokine affecting the expression of multiple other chemokines, we have chosen to focus on just two representative examples: RANTES (regulated on normal T cell expressed and secreted) and MCP-1 (Monocyte chemo-attractant protein). Here, we present updated information on their expression levels and regulation on three different levels: 1) systemic effects on maternal allogeneic response; 2) local effects on endometrial cells; and 3) during an early stage of the feto-maternal dialogue. For each of the three levels, we analyzed data from both fertile women and patients having experienced recurrent spontaneous abortions as representative of physiological and pathological situations respectively.